ENERGY EFFICIENT DRIVERS OF SUPPORT MECHANISMS (Transport systems and technologies, 2018)
The reduction of energy costs for rail transportation is ensured by optimizing the operation of all systems and locomotive mechanisms, in particular, venetilisers, compressors, generators, hydrostatics pumps. Unlike traditional technology for controlling auxiliary actuators using by-pass, Voith Flow System regulates the operation of the machines, directly controlling the performance of oil pumps, which significantly reduces energy consumption and improves the control of the drive system as a whole.
Keywords: auxiliary aggregates, hydrostatic drives, bypass, pro-ductivity of the oil pump, energy efficient drives.